IDENTIFIKASI KETERAMPILAN PROSES SAINS (KPS) DASAR PRA IMPLEMENTASI EKSPERIMEN VIRTUAL DI SMAN 5 PEKANBARU - Vebby Oksaviona; Zulirfan Zulirfan; Naila Fauza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This quasi-experimental research aims to identify the basic Science Process Skills (KPS) of students pre-implementing virtual experiments at SMAN 5 Pekanbaru. The instrument used was a basic KPS test in the form of multiple choices. The research stages include the preparation stage and the implementation stage. The preparatory stage includes identifying problems, formulating problems, preliminary studies, determining samples, and making a test. Meanwhile, the implementation stage includes data collection and data analysis. There were 48 students of class XI MIPA SMAN 5 Pekanbaru who participated in a series of activities in this study. There are four aspects chosen by researchers such as observation, classification, prediction, and communication. The results showed that the basic KPS results of the pre-implementation virtual experiment students were in the high category. Class XI MIPA 6 which produces an average score of basic KPS of 61.54. As well as class XI MIPA 7 which produces an average KPS score of 69.95.Keywords: Science Process Skills, Virtual Experiment.